STRENGTHENING DIGITAL START-UP DYNAMIC CAPABILITIES IN MALANG CITY THROUGH DESIGN THINKING AND ENTREPRENEURSHIP ORIENTATION. - Widi Dewi Ruspitasari; Widiya Dewi Anjaningrum; Mega Mirasaputri Cahyanti (Manajemen Bisnis, 2020)
Digital start-up is one part of the creative economy that is currently growing rapidly in Malang town. Looking at this rapidly changing environment in the era of the industrial revolution 4.0, it is important for digital start-ups to improve dynamic capabilities. The purpose of this study was to determine the effect of design thinking and entrepreneurial orientation on dynamic digital start-up capabilities. A total of 100 start-up actors have been selected as research samples. Quantitative data collected through questionnaires were analyzed using PLS analysis. The results showed that both design thinking and market orientation had a great influence on dynamic digital start-up capabilities. The strongest factor in the design thinking is the emphatize process so that the ability of start-ups to feel the environment and understand customer needs and market dynamics better than competitors. While the strongest factor in entrepreneurship is the courage to act to achieve goals so that start-ups are able to face market competition. Suggestions for further research is need to focus on two weaknesses factors, there are, the process of ideas in conducting design thinking and the lack of initiative in initiating innovative actions, because the innovation today is urgently needed to win the market competition.